SOCIAL AND PHILOSOPHICAL ASPECTS OF ADMINISTRATIVE MANAGEMENT RELATIONS IN THE CONTEXT OF MODERN SOCIAL CHALLENGES - Sidorkina, Olena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
administrative management of social activity. The aim and tasks are to consider the philosophical aspects of administrative management relations in the context of modern social challenges to implement the main provisions of the concept of sustainable development in practice. Research methods consist primarily of the theoretical foundations of the dialectical approach in interpreting the interaction of the subject and the object of social administration, the principles of the systemic approach. Also, the author relied on philosophical and sociological studies of social deviations, the states of social consciousness. Research results. The humanization of the management subsystem with the development of elements of social self-organization can be considered as one of the ways to successfully overcome modern challenges, the formation of positive feedback between individuals, teams and society as a whole, and should also be a mandatory component of all existing and future social projects. It is the principles of humanism, positive systemic social relations, the effective use of socially significant information and communication, the democratic nature of the distribution of social influences and opportunities for self-organization that will serve as the meaningful content of social transformation, which is the path to the survival of humanity. Discussion. The entire set of administrative management interactions is understood as subject-object interaction with a complex, multi-level structure. The administrative management process is carried out in relation to human collectives, extends to natural processes (ecological management), as well as technology, the placement of productive forces. Conclusions. In the conditions of modern societal challenges, which have a systemic nature, the humanization of the administrative management subsystem with the development of elements of social self-organization can be considered as one of the ways to successfully overcome modern challenges, to arrange positive feedback between individuals, collectives and society as a whole, and to be mandatory an essential component of all current and future social projects. From a philosophical point of view, the ideal of the historical development of social administrative management can serve as a method of collective social self-management, in which the subject and the object of management form an organic functional unity. Humanization of social relations, humanism of social administrative management is the main principle of building a future dialogic environment in interstate and intercultural relations.